The Effect of Physical Activity on Weight Decrease of Obesity Students at Smk Negeri 3 Salatiga - Angkit Kinasih; Kristiawan Prasetyo Agung Nugroho; Nur Sugiharso (Universitas Negeri Medan, 2020)
Adolescent obesity occurs because it requires more nutritional intake to support the growth process and sometimes without being balanced with a healthy lifestyle and lack of physical activity. The research objective was to determine the effect of physical activity on weight loss of obese students at SMK Negeri 3 Salatiga. This type of quantitative research with a quasi-experimental model. There were 20 students in class X and XI with BMI> 27 kg / m2. Physical activity undertaken is a pattern of aerobic physical exercises such as jogging, push ups, and sit ups for 3 times a week with a duration of 30 minutes for 1 month. Analysis of research data includes the stages of univariate data analysis including descriptive information from respondents and analysis of bivariate data using Paired Samples T Test. The results of this study have reduced body weight by 3% with physical exercise in the form of jogging, push ups, and sit ups.